The Effect of SBS Content on The Warm Asphalt Concrete Mixtures Performance (Journal of University of Babylon for Engineering Sciences, 2017)
Warm mix asphalt (WMA) represents a number of technologies used to decrease the mixing and compaction temperature.  The reduction in temperature has many advantages such as: lower cost to produce such as mixtures, and environmental effects. In Iraq the WMA technology consider a new technology can be sued for the next years. The main objective for this research is to study the effect of polymer on the performance of WMA. In this study, three kinds of asphalt mixtures were used: Hot Mix Asphalt (HMA), Warm Mix Asphalt (WMA), and Polymer Modified WMA. The WMA has produced by adding Aspha- min® at rate 0.3%, and for WMA modified by SBS they contain SBS with rate (0.5-3.5) %.The performance tests consist on: Indirect Tensile Strength Ratio Test (moisture susceptibility), and Wheels – Track Test (rutting resistance). The results of these tests have indicated that, performance of HMA better than WMA, and the adding of SBS to WMA improve their performance. However, the using of SBS at rate (3%) and more improve the WMA performance against moisture damage and rutting.